Sigmoid gallstone ileus: A case report and literature review in Japan. (2018) - Inukai, Koichi; Uehara, Shuhei; Miyai, Hirotaka; Takashima, Nobuhiro; Yamamoto, Minoru; Kobayashi, Kenji; Tanaka, Moritsugu; Hayakawa, Tetsushi
Highlights: We present a unique case of gallstone ileus with inguinal hernia. A one-stage operation can be considered for patients with gallstone ileus associated with cholecystocolonic fistula. A review of the literature pertaining to colonic gallstone ileus is presented. Abstract: Introduction: Gallstone as a cause of bowel obstruction is rare, and its occurrence in the colon is very infrequent. Here, we report the case of sigmoid gallstone ileus treated with one-stage operation. Case presentation: A 65-year-old man visited our hospital because of abdominal pain and nausea. On the basis of the results of computed tomography, the patient was diagnosed with sigmoid gallstone ileus through cholecystocolonic fistula, and an emergency laparotomy was performed. Enterolithotomy, cholecystectomy, and fistula closure were performed in one-stage operation. Postoperatively, the patient developed biliary leakage, which rapidly recovered with conservative therapy. Discussion and conclusion: The surgical treatment of gallstone ileus remains controversial. For postoperative infection control, one-stage operation can be considered for patients with gallstone ileus associated with cholecystocolonic fistula.